Quantification of Farnesol From Red and Green Leaves of Syzygium campanulatum - Yap, Qing Yang (2017)
S. campanulatum, also known as “kelat paya” can grow young leaves with various colors. Due to this characteristic, S. campanulatum is commonly used in landscaping. S. campanulatum under family of Myrtaceae and genus of Syzygium which is rich in secondary metabolites among which is farnesol. Farnesol produces a floral scent and widely is used as an ingredient in fragrance. Farnesol was found to have anti-fungal, anti-microbial and anti-tumour properties. The aims of this study were to determine the suitable wavelength to detect the maximum absorbance of farnesol in S. campanulatum extracts, to qualify the farnesol using four extraction solvents; namely hexane, methanol, acetone and sterile dH2O in red leaf of S. campanulatum and to compare and quantify of the farnesol content between red and green leaves of S. campanulatum. Wavelength scan showed the optimal wavelength to detect farnesol was 290 nm. TLC was used to separate farnesol from other compounds in crude leaf extracts of S. campanulatum. The distance travelled by the sample corresponding to farnesol standard solution indicated the presence of farnesol. Apart from comparing distance travel by compound, colour development after stained with p-anisaldehyde also used to verify isolation of farnesol. The silica was scrapped off from TLC plate and re-extracted with hexane and this extract was known as TLC-isolated extracts. The A290 of TLC-isolated extracts of red and green leaves were analysed and interpolated their concentration using farnesol standard. The hexane extract of red leaf contained higher concentration of farnesol compared with hexane extract of green leaf. t-test result showed there was significant different between the mean of farnesol content of red leaf and green leaf of S. campanulatum.